A comprehensive neuromonitoring approach in a large animal model of cardiac arrest. Issue 1 (28th January 2022) - Annoni, Filippo; Peluso, Lorenzo; Hirai, Lucas Akira; Babini, Giovanni; Khaldi, Amina; Herpain, Antoine; Pitisci, Lorenzo; Ferlini, Lorenzo; Garcia, Bruno; Taccone, Fabio Silvio; Creteur, Jacques; Su, Fuhong
Abstract: Background: Anoxic brain injuries represent the main determinant of poor outcome after cardiac arrest (CA). Large animal models have been described to investigate new treatments during CA and post‐resuscitation phase, but a detailed model that includes extensive neuromonitoring is lacking. Method: Before an electrically‐induced 10‐minute CA and resuscitation, 46 adult pigs underwent neurosurgery for placement of a multifunctional probe (intracranial pressure or ICP, tissue oxygen tension or PbtO2 and cerebral temperature) and a bolt‐based technique for the placement and securing of a regional blood flow probe and two sEEG electrodes; two modified cerebral microdialysis (CMD) probes were also inserted in the frontal lobes and accidental misplacement was prevented using a perforated head support. Result: 42 animals underwent the CA procedure and 41 achieved the return of spontaneous circulation (ROSC). In 4 cases (8.6%) an adverse event took place during preparation, but only in two cases (4.3%) this was related to the neurosurgery. In 6 animals (13.3%) the minor complications that occurred resolved after probe repositioning. Conclusion: Herein we provide a detailed comprehensive neuromonitoring approach in a large animal model of CA that might help future research. Abstract : The figures displays multiple neuromonitoring devices in place to allow simultaneous measurements of multiple brain‐derived parameters during cardiac arrest and post‐resuscitation period.